2000
DOI: 10.4319/lo.2000.45.8.1689
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and vertical difference in negative and positive effects of grazers on heterotrophic bacteria in Lake Biwa

Abstract: Grazers affect prey abundance negatively through grazing and positively through releasing nutrients and substrates. In the present study, the relative importance of these positive and negative effects of grazers on bacterial abundance was examined seasonally at 2.5 m and 30 m depths in Lake Biwa. We used a method by Elser and Goldman to estimate in situ growth rate, grazing rate, and the fraction of growth rate that was stimulated by grazers smaller than 100 m. At 2.5 m, the bacterial grazing rate showed clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…In these conditions, grazing was a factor controlling bacterial abundance, particularly during summer. This is consistent with the results of several other studies which showed that bacteriovory is highly dependent on water temperature, with a maximum in summer (Marrase et al 1992;Shiah and Ducklow 1994;Vaque et al 1994;Gurung et al 2000). A marked increase in bacterial Table 3 Simultaneous effects of chl a and temperature on bacterial abundance in the surface layers (0-20 m), and bacterial production and temperature on heterotrophic nanoflagellates (HNF) in the layers between 20 and 30 m depth at station Stončica.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In these conditions, grazing was a factor controlling bacterial abundance, particularly during summer. This is consistent with the results of several other studies which showed that bacteriovory is highly dependent on water temperature, with a maximum in summer (Marrase et al 1992;Shiah and Ducklow 1994;Vaque et al 1994;Gurung et al 2000). A marked increase in bacterial Table 3 Simultaneous effects of chl a and temperature on bacterial abundance in the surface layers (0-20 m), and bacterial production and temperature on heterotrophic nanoflagellates (HNF) in the layers between 20 and 30 m depth at station Stončica.…”
Section: Discussionsupporting
confidence: 90%
“…The relative importance of resources derived from phytoplankton was shown to be higher in the oligotrophic open sea than in coastal and estuarine areas, where allochtonous inputs of organic matter present the dominant source of substrates for microorganisms. Heterotrophic nanoflagellates (HNF) have been identified as a major source of bacterial mortality in aquatic ecosystems Sherr 1994, 2001;olić and Krstulović 1994;Christaki et al 2001), but predation pressure was found to be dependent on temperature and the trophic state of the studied area (Shiah and Ducklow 1994;Vaque et al 1994;Krstulović et al 1997;olić et al 1998, 2001Gurung et al 2000). The effects of these factors are not always clear, as they can act simultaneously, changing their relative importance over space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Densities of HNF shaped similarly to those reported in wetlands (Sinistro, 2009;Straskrábová et al, 2011). Their abundance was correlated with bacteria, a phenomenon often observed in aquatic ecosystems (Simon et al, 1998;Gurung et al, 2000). Mean abundances of ciliates were similar to those observed in various peatbog ecosystems (Mieczan, 2009(Mieczan, , 2010Quiroga et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…While each one of these methods, e.g. size fractionation, has inherent advantages and limitations, some values may be underestimated if the predator-free environment (< 2 µm) is taken into consideration, as the grazing activity of protozoa may stimulate bacterial growth (Chase & Price 1997, Gurung et al 2000, Metzler et al 2000. However, Gasol & Moran (1999) had an opposite view and showed that the size fractionation method may cause cell damage, which may then increase the amount of dissolved organic matter present, inducing a possible increase in bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…and mean flagellate was estimated using the following equation (Gurung et al 2000 ) was calculated by dividing the ingestion rate by the concentration of bacteria or Synechococcus spp.…”
Section: Samplingmentioning
confidence: 99%